Penggunaan Model Pembelajaran Inside Outside Circle (IOC) Dalam Meningkatkan Keterampilan Berbicara Siswa: Penelitian Tindakan Kelas pada Siswa Kelas X IPS 3 SMA Negeri 23 Bandung - Karyanti, Keni Suarnia (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to see that the use of the Inside Outside Circle (IOC) Learning Model Can Improve Students' Speaking Skills in Kennenlernen Material, German Language and Literature subjects in class X IPS 3, SMA Negeri 23 Bandung, Semester 1, 2017-2018 academic year. . Classroom Action Research (CAR) was conducted in class X IPS 3 with a total of 31 students, consisting of 13 male students and 18 female students. The data collection techniques used in Classroom Action Research are as follows: 1) Observation is used to collect data about improving speaking skills on the Kennenlernen material for 2 cycles using observation sheets. 2) Tests, pre-tests and post-tests are used to obtain data on student learning outcomes for success and measure the level of student learning knowledge. 3) Discussion with colleagues to reflect on the results of each cycle of Classroom Action Research (CAR). Based on the results of the overall discussion of Class Action Research (CAR) data, it can be concluded that the use of the